2012
DOI: 10.1136/annrheumdis-2012-eular.2824
|View full text |Cite
|
Sign up to set email alerts
|

FRI0367 BCX4208 added to allopurinol increases response rates in patients with GOUT who fail to reach goal range serum uric acid on allopurinol alone: A randomized, double-blind, placebo-controlled trial

Abstract: Background BCX4208, a novel purine nucleoside phosphorylase inhibitor, blocks uric acid production at a step preceding xanthine oxidase and synergistically reduces serum urate concentration (sUA) in gout patients when combined with allopurinol1. Objectives To assess the sUA response to the addition of placebo or one of 4 doses of BCX4208 to 300 mg/d allopurinol in gout patients with sUA ≥6.0 mg/dL on allopurinol alone. Primary endpoint was the proportion of BCX4208-treated subjects achieving sUA goal range (<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…An initial 12-week RCT comparing four different doses of ulodesine (5, 10, 20 and 40 mg/day) with allopurinol 300 mg/day to allopurinol monotherapy showed a significantly greater proportion of patients achieving the SU goal, with a safe profile and adequate tolerance to the combination [Becker et al 2013]. The 24-week extension which included 160 patients from the original study showed that by the end of trial, 40%, 50%, 46% and 55% of the patients receiving the 5, 10, 20 and 40 mg/day of ulodesine, respectively, achieved a goal SU less than 6 mg/dl [Hollister et al 2013].…”
Section: New Therapies In Developmentmentioning
confidence: 99%
“…An initial 12-week RCT comparing four different doses of ulodesine (5, 10, 20 and 40 mg/day) with allopurinol 300 mg/day to allopurinol monotherapy showed a significantly greater proportion of patients achieving the SU goal, with a safe profile and adequate tolerance to the combination [Becker et al 2013]. The 24-week extension which included 160 patients from the original study showed that by the end of trial, 40%, 50%, 46% and 55% of the patients receiving the 5, 10, 20 and 40 mg/day of ulodesine, respectively, achieved a goal SU less than 6 mg/dl [Hollister et al 2013].…”
Section: New Therapies In Developmentmentioning
confidence: 99%
“…Two Phase II clinical trials have shown promising results regarding urate-lowering effect in both as monotherapy and in combination with allopurinol ( Table 5) [90]. In the 12-week randomized controlled trial, in 82 gout patients, the response rates to 5, 10, 20 and 40 mg ulodesine (BCX4208) compared with allopurinol 300 mg were 45, 33, 39 and 49%, respectively [91]. In the 24-week extension study, response rates for doses 5, 10 and 20 mg were found to be 40, 50, 45 and 65%, respectively, compared with placebo response of 25% [92].…”
Section: Urate Synthesis Inhibitors 321 Ulodesine (Bcx4208)mentioning
confidence: 98%
“…Hypoxanthine is the precursor of xanthine and a substrate of xanthine oxidase ( Figure 1 ). Ulodesine, a PNP inhibitor, was effective as single agent [ 86 ] and in combination with allopurinol [ 87 ]. In the combination treatment arm, 40–55% of patients achieved the target urate level, which compared favorably to 25% in the allopurinol arm [ 88 ].…”
Section: Therapeutic Approaches To Treat Hyperuricemia and Goutmentioning
confidence: 99%